(untitled) - Watson, Burton (New York, 1961)
In this volume deal principally with the reign of Emperor Wu, the period of Ssu-ma Ch'ien's own life-time. The historian is here no longer copying and systematizing the written accounts of ancient China, as he had done in the chapters on pre-Ch'in history, nor relatinf the somewhat romanticized tales of the founding and early days of the Han that had been handed down to him. he is writing about "the pesent emperor". the ruler at whose court he spent his adult life, about the nobles and ministers he knew there, about his freinds, and about his enemies.
Keywords: China; History